Decreased Legionnaires' disease incidence in the United States during the COVID-19 pandemic, 2020-2022 - Devarajulu Reddy; Diviya Alex; Christina Zonunmawii; Sabarish Prabhu; D.N. Dhiliban (University of New South Wales, 2023)
Legionnaires' disease was first detected in 1976 when an outbreak occurred in Philadelphia, USA. The number of cases reported to the Centre for Disease Control (CDC) has been on the rise since 2000, likely due to expanded diagnostic testing and public awareness of symptoms. There was a notable decline of confirmed cases during the first years of the COVID-19 pandemic. Surveillance is important to understand the transmission, pathogenesis, and complications, and to quickly identify the outbreaks, new cases and epidemiologic links between cases. The EPIWATCH system scans vast amounts of open-source data to supplement surveillance when there is a lack of available case data. EPIWATCH reported approximately 28 cases during September to December 2020, 349 cases in 2021 and 114 cases during January to October 2022, which is a decrease in case numbers, possibly due to underreporting during the ongoing COVID-19 pandemic. Annual case numbers may be 1.8 to 2.7 times higher than reported, due to potential underdiagnosis and the requirement for confirmation of infection source before a diagnosis can be made. Key words: Legionella; Legionnaires' disease; outbreak, USA